Do undergraduate heathcare students have to disclose their academic status to patients when involved in their care? - Van Niekerk, Martha Susanna (My University, 2014)
Using patients in the training of healthcare students is required by the World Federation of Medical Educators. South African legal instruments such as the Constitution and the National Health Act recognise patients’ right to autonomy. This descriptive, analytical study investigated whether patients should be informed that the person involved in their care is a student. International studies and the ethical guidelines of regulating bodies support informing patients of the academic status of persons participating in their care. While patients are willing to participate in the training of healthcare students, they do not waive their right to informed consent. South African health care practitioners are increasingly required to disclose non-medical information to patients, such as treatment costs. Patients should be informed about the academic status of persons involved in their care and have the right to refuse to participate in medical education. The HPCSA should draw up guidelines to support this.
Keywords: Truth Disclosure; Ethics